The first-time manager - Belker, Loren B.; Topchik, Gary S. (New York, N.Y. : AMACOM, 2005)
A true management classic with 200,000 copies sold!
Preface; Acknowledgments; Introduction; 1 The Road to Management; 2 Starting Out; 3 Building Trust and Confidence; 4 Show Your Appreciation; 5 Being an Active Listener; 6 The New Manager's Job and Pitfalls to Avoid; 7 Dealing with Your Superiors; 8 Choosing a Managerial Style of Your Own; 9 Building Team Spirit; 10 Managing Problem Employees; 11 Hiring and Interviewing; 12 Training Team Members; 13 Managing Change Dealing with Resistance; 14 Disciplining the Employee; 15 Oh My God I Can't Fire Anyone; 16 Having a Legal Awareness; 17 No Secrets; 18 The Human Resources Department.
Includes index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Supervision of employees; Office management; Personnel -- Supervision; Bureaux -- Organisation; BUSINESS & ECONOMICS -- Workplace Culture; BUSINESS & ECONOMICS -- Human Resources & Personnel Management; Office management; Supervision of employees